Vibration Analysis and Topology Optimization of Gearbox of Electric Vehicle - Wang Haoran; Fang Yuan; Zhang Tong (Jixie chuandong)
According to an electric automotive gearbox,the dynamics simulation of the reducer two-stage gear transmission is established in ADAMS and the dynamic loads of bearing seat are obtained.The finite element model（ FEM） of gearbox housing is established,the nature frequency and vibration mode are obtained through the analysis of the modal.The data are loaded into the finite element model and the modal frequency response analysis is carried out.Then,the topology optimization of gearbox housing is conducted,the results show that the vibration response amplitudes are significantly reduced.